Management of anaemia in pre‐term infants. (6th October 2019) - Saito‐Benz, Maria; Flanagan, Peter; Berry, Mary J.
Summary: Pre‐term infants have one of the highest transfusion requirements within the hospital‐setting. The vast majority of blood transfusions performed in Neonatal Intensive Care Units (NICUs) are for medically stable pre‐term infants with anaemia of prematurity, with the aim of improving oxygen delivery to the vital organs during the crucial phase of growth and development. However, despite the frequency of transfusion in this population, the potential benefits and harms of 'top up' transfusion are not fully understood, leading to practice variation between clinicians, institutions and countries. Significant advances have been made in the prevention of anaemia of prematurity, with recent emphasis on optimising infants' circulatory volume at birth via placental transfusion and preserving infants' own blood volume through innovative minimal sampling techniques. More research is urgently needed to establish optimal transfusion thresholds for these high‐risk pre‐term infants, for whom benefits as well as adverse outcomes may have consequences that extend for decades throughout the recipients' life‐course. In this review, we will discuss some of the consensus and controversies regarding optimal management of anaemia in pre‐term infants and highlight potential areas for future research.